2016
DOI: 10.1186/s12872-016-0246-y
|View full text |Cite
|
Sign up to set email alerts
|

Urine proteomics in the diagnosis of stable angina

Abstract: BackgroundWe have previously described a panel of 238 urinary polypeptides specific for established severe coronary artery disease (CAD). Here we studied this polypeptide panel in patients with a wider range of CAD severity.MethodsWe recruited 60 patients who underwent elective coronary angiography for investigation of stable angina. Patients were selected for either having angiographic evidence of CAD or not (NCA) following coronary angiography (n = 30/30; age, 55 ± 6 vs. 56 ± 7 years, P = 0.539) to cover the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 34 publications
(16 reference statements)
0
14
0
Order By: Relevance
“…This database is regularly updated, currently storing datasets from over 50 000 urine samples (healthy controls and patients with different diseases), encompassing endogenous peptide signals and respective sequence information . Multiple studies have shown that such endogenous urinary peptides combined in classifiers represent powerful tools in the diagnosis and clinical assessment of several diseases such as kidney diseases, different cancers, and cardiovascular diseases . However, less is known about the origin of these peptides.…”
Section: Introductionmentioning
confidence: 99%
“…This database is regularly updated, currently storing datasets from over 50 000 urine samples (healthy controls and patients with different diseases), encompassing endogenous peptide signals and respective sequence information . Multiple studies have shown that such endogenous urinary peptides combined in classifiers represent powerful tools in the diagnosis and clinical assessment of several diseases such as kidney diseases, different cancers, and cardiovascular diseases . However, less is known about the origin of these peptides.…”
Section: Introductionmentioning
confidence: 99%
“…However, proteome studies are still rare in relation to CAD, mostly due to the complex methodology involved. There have been some investigations in the past few years, aiming at characterizing the proteomes of several CAD-related tissues and cell types, including human arterial smooth muscle cells ( 71 ), platelets ( 72 ), as well as body fluids such as urine ( 73 ).…”
Section: Integrating Genetic Variation and Proteomementioning
confidence: 99%
“…In cardiovascular disease both approaches have been deployed to lead to a better global understanding of coronary artery disease [27]; or the rapid targeted analysis of the concentrations of angiotensin II (Ang II), Ang-(1–7), Ang III, and Ang IV [28]. In addition it is also possible to analyze native peptides, where no digestive enzyme is used in the preparation, such as the diagnostic biomarkers present in urine for coronary artery disease [29,30]. …”
Section: Proteomicsmentioning
confidence: 99%